Catalytic activity of hierarchical structure based on Ni-Al layered double hydroxide. Issue 1 (May 2020) - Aliev, A; Sharafieva, Z; Popkov, A; Isakov, D; Sultanaliev, D
Abstract: In this paper, the characteristics of the composition and structure of NiAl layered double hydroxide as a precursor element of the catalytic system are determined. According to x-ray fluorescence analysis, nickel content in layered double hydroxide was 86%, aluminum - 13%. The obtained elements of the catalytic system have a specific surface area of 158 m 2 /g and stability at high temperatures and pressures. The results of the study of catalytic activity in cracking reactions of C11 -C22 higher alkanes in the presence of Ni-Al layered double hydroxide at temperatures of 450°C and 500°C and a flow rate of 0.5 ml/min, with a ratio of raw materials to the catalyst equal to 30 are given. The products of catalytic conversion of the initial mixture of alkanes are C7 -C14 normal- and isoalkanes. According to IR spectroscopy, unsaturated compounds were formed as the reaction products.